Kehamilan Di Luar Nikah Dalam Perspektif Katolik: Studi Berdasarkan Kitab Hukum Kanonik (KHK) (Jurnal Hukum Magnum Opus, 2023)
This study aims to provide a discussion regarding the resolution of problems of premarital sexual relations which lead to pregnancy out of wedlock according to the perspective of the KHK and the Catholic Church's understanding of marriage. The research method used is qualitative research with a literature study approach and interpretive phenomenological analysis from Paul Ricoeur. This study found that pregnancy outside of marriage is not an obstacle to marriage (Kan. 1083 – 1094). However, it is necessary to pay further attention to the marriage agreement, so that defects do not occur in the marriage agreement (Can. 1095 – 1107). For this reason, there needs to be a persuasive dialogue between women who are pregnant out of wedlock and their marriage partners. In addition, children who are the fruit of pre-marital pregnancies are still entitled to their rights as a child without being excluded from anything. This is because pregnancy outside of marriage is a moral problem with regard to sexual relations outside of marriage. This moral problem does not always have to be resolved by marriage, especially when the marriage occurs because of compulsion which will cause the marriage agreement to be flawed according to the KHK. Thus it is necessary to form a solution based on a joint decision. Keywords: code of canon law; marriage law; sexual relations; unwed pregnancy Abstrak Penelitian ini bertujuan untuk memberikan pembahasan mengenai penyelesaian persoalan relasi seksual pra nikah yang berujung pada kehamilan di luar nikah menurut perspektif KHK dan paham pernikahan Gereja Katolik. Metode penelitian yang digunakan adalah penelitian kualitatif dengan pendekatan studi pustaka dan analisis fenomenologi interpretatif dari Paul Ricoeur. Penelitian ini menemukan, kehamilan di luar nikah tidak menjadi halangan pernikahan (Kan. 1083 – 1094). Namun demikian perlu diperhatikan lebih lanjut mengenai kesepakatan nikah, supaya tidak terjadi cacat dalam kesepakatan nikah (Kan. 1095 – 1107). Untuk itu perlu ada dialog persuasif antara perempuan yang hamil di luar nikah dengan pasangan nikah. Selain itu anak yang merupakan buah dari kehamilan pra nikah tetap berhak mendapatkan haknya sebagai seorang anak tanpa dikecualikan dari apa pun. Hal ini dikarenakan kehamilan di luar nikah adalah problem moral berkenaan dengan relasi seksual di luar nikah. Problem moral ini tidak selalu harus diselesaikan dengan pernikahan terlebih ketika pernikahan itu terjadi karena keterpaksaan yang akan menyebabkan perjanjian nikah menjadi cacat menurut KHK. Dengan demikian perlu dibentuk suatu penyelesaian berdasarkan keputusan bersama. Kata kunci: hukum pernikahan; kehamilan pranikah; kitab hukum kanonik; relasi seksual